Characterizing academic performance in pediatric acute lymphoblastic leukemia with population‐based achievement tests. Issue 9 (30th September 2021) - Al‐Kaylani, Hend M.; Reasoner, Erin E.; Loeffler, Bradley T.; Mott, Sarah L.; Madasu, Susan; Liu, Audrey; Langbehn, Kathleen; Conrad, Amy L.; Dickens, David; Grafft, Amanda; Harshman, Lyndsay; Modi, Arunkumar J.; et al.
Abstract: Background: Recent shifts from radiation to chemotherapy‐based treatment for acute lymphoblastic leukemia (ALL) have contributed to reduced long‐term morbidity. Despite this, ALL survivors remain at increased risk for long‐term cognitive impairments. Aim: To identify demographic and treatment factors associated with school performance in pediatric survivors of ALL. Methods: We collected standardized test scores for reading, math, and science obtained in a school setting from grades 3–11 in 63 ALL survivors (46.0% boys). Most participants were assessed across multiple grades (median number of grades n = 5, range 1–7), and 269 observations were considered in the analyses. Treatment exposures were extracted from medical records. Socio‐economic status was estimated using participation in free/reduced lunch programs at school. Mixed effects linear regression models were conducted to determine factors associated with school performance. Results: ALL survivors' scores were comparable to state norms on reading, math, and science performances. On multivariable analysis, participation in free/reduced lunch programs was significantly associated with lower reading scores ( β = −12.52; 95% CI −22.26:−2.77, p = .01). Exposure to radiation during treatment was also associated with lower reading test scores ( β = −30.81, 95% CI −52.00:−9.62, p = .01). No significant associations between demographics and treatment parameters were observed for math and science test scores. Conclusions: We utilized population‐based achievement tests conducted from grades 3–11 to characterize school performance in ALL survivors. Our results imply that survivors with low socio‐economic status and those exposed to radiation during treatment could benefit from early monitoring and intervention to maximize academic success.